2020
DOI: 10.1002/pts.2536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycerol and sorbitol on optical, mechanical, and gas barrier properties of potato peel‐based films

Abstract: Potato peel is a by-product of potato-based food production and seen as a zero-or negative-value waste of which millions of tons are produced every year. Previous studies showed that potato peel is a potential material for film development when plasticized with 10% to 50% glycerol (w/w potato peel). To further investigate potato peel as a film-forming material, potato peel-based films containing the plasticizer sorbitol were prepared and investigated on their physicochemical properties in addition to films con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
2
11
0
1
Order By: Relevance
“…[6][7][8][9] The functionality of protein-based films depends on the molecular structures, which leads to different mechanical and barrier properties. [10,11] This study aims at investigating the potential of a pea protein isolate-based material to form films with interesting properties by a protein extrusion process. [12] There are several studies that have successfully investigated the properties of pea protein-based materials, but with different processing techniques and different applications.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The functionality of protein-based films depends on the molecular structures, which leads to different mechanical and barrier properties. [10,11] This study aims at investigating the potential of a pea protein isolate-based material to form films with interesting properties by a protein extrusion process. [12] There are several studies that have successfully investigated the properties of pea protein-based materials, but with different processing techniques and different applications.…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al. [ 21 ] found that the film thickness of potato starch film increased with the addition of glycerol and sorbitol. Similarly, in the case of the film derived with cassava starch, it is found that film thickness increased when different types of plasticizers: fructose, tri‐ethylene glycol, and urea, were incorporated.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the brittleness of alginate films, some studies combine more than one plasticizer, such as glycerol, palmitic acid, β-cyclodextrin and glycerol monostearate used in film formulations (Fan et al, 2009). Miller et al, (2021) investigated the effect of glycerol and sorbitol plasticizers on potato-based film and discovered that as plasticizer concentration increased, so did the film's water vapor and oxygen permeability. A glycerol-containing film had higher water vapor and oxygen permeabilities than a sorbitol-containing film (Miller et al, 2021).…”
Section: Plasticizersmentioning
confidence: 99%
“…Miller et al, (2021) investigated the effect of glycerol and sorbitol plasticizers on potato-based film and discovered that as plasticizer concentration increased, so did the film's water vapor and oxygen permeability. A glycerol-containing film had higher water vapor and oxygen permeabilities than a sorbitol-containing film (Miller et al, 2021).…”
Section: Plasticizersmentioning
confidence: 99%